The holy wars of King Wladislas and Sultan Murad - Jefferson, John.
1 online resource (ix, 514 pages)
Keywords: The Holy Wars of King Wladislas and Sultan Murad comprises the first detailed treatment of the pivotal conflict between the Ottomans and Christendom from 1438-1444. Beginning with the Council of Florence and renewed Ottoman expansion it covers the election of Wladislas, the rise of John Hunyadi and the factional politics of the Porte. \'The author recounts the major campaigns including Hunyadi's victories in 1442 as well as the Long March and Varna expeditions of 1443/44. He also gives a thorough description of the armies, their tactics and strategy. Dr. Jefferson's work is the first to make full use of both Ottoman and Christian sources, and not only corrects persistent misconceptions but provides the fullest picture of this conflict to date.